Association between propofol dose and 1-year mortality in patients with or without a diagnosis of solid cancer. (March 2020) - Schaefer, Maximilian S.; Raub, Dana; Xu, Xinling; Shaydenfish, Denys; Teja, Bijan; Chhangani, Khushi; Grabitz, Stephanie D.; O'Gara, Brian; Kienbaum, Peter; Houle, Timothy T.; Landoni, Giovanni; Eikermann, Matthias
Abstract: Background: Preclinical data suggest suppression of cancer proliferation by propofol, and retrospective studies suggest improved survival after cancer surgery with propofol-based anaesthesia. Methods: To determine whether propofol dose administered for anaesthesia is associated with 1-yr mortality in patients with and without a diagnosis of solid cancer, we analysed adult patients undergoing monitored anaesthesia care or general anaesthesia at two academic medical centres in Boston, MA, USA. Logistic regression with interaction term analysis was applied with propofol dose (mg kg −1 ) as primary and diagnosis of solid cancer as co-primary exposure, and 1-yr mortality as the primary outcome. Results: Of 280 081 patient cases, 10 744 (3.8%) died within 1 yr. Increasing propofol dose was associated with reduced odds of 1-yr mortality (adjusted odds ratio [aOR] 0.93 per 10 mg kg −1 ; 95% confidence interval [CI]: 0.89–0.98; absolute risk reduction fifth vs first quintile 0.5%; 95% CI: 0.2–0.7). This association was modified by a diagnosis of solid cancer ( P <0.001 for interaction). Increasing propofol dose was associated with reduced odds of 1-yr mortality in patients without solid cancer (aOR: 0.78; 95% CI: 0.71–0.85), but not in patients with solid cancer (0.99; 0.94–1.04), a finding that was replicated when examining 5-yr mortality. Conclusions: Increasing propofol dose is associated with lower 1-yr mortality in patients without, but not in patients with, a diagnosis of solid cancer. We found evidence for competing effects, modifying the association between propofol dose and mortality.